INCREASED URINARY 8-OXO-7,8-DIHYDRO-2′-DEOXYGUANOSINE EXCRETION IN A SAMPLE OF EGYPTIAN CHILDREN WITH BETA THALASSEMIA MAJOR: MARKER FOR LIPID PEROXIDATION-INDUCED DNA DAMAGE - Elabd, Mona A; Zeid, Dina Abu; Elhady, Marwa A; El Wakeel, Maged A.; El-kassas, Ghada M.; Sabry, Rania N; Awadallah, Eman (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The objective of this research was to evaluate oxidative stress status in children with β-thalassemia major. Methods: Our study was conducted in children with β-thalassemia aged from 5 to 15 years. Investigate the urinary excretion of human 8-oxo-7,8- dihydro-2′-deoxyguanosine, which will be analyzed by enzyme-linked immunosorbent assay. To investigate serum levels of antioxidant enzymes include glutathione s-transferase (GST) and catalase (CAT). Results: We found a significant elevation of the urinary 8-oxo-7,8-dihydro-2′-deoxyguanosine level with p=0.001 compared to control group, a significant reduction of both GST and CAT p=0.05 and 0.03, respectively, compared to control group. There was a significant negative correlation between urinary 8-oxo-7,8-dihydro-2′-deoxyguanisine and CAT level, r=−0.378, p=0.016, hemoglobin - r=−0.610, p=0.001, hematocrit (%) - r=−0.478, p=0.002, while a significant positive correlation between urinary 8-oxo-7,8-dihydro-2′-deoxyguanisine and alanine aminotransferase - r=0.547, p=0.001, and serum ferritin - r=0.391, p=0.013. There was a significant negative correlation between CAT and serum ferritin - r=−0.320, p=0.44. Conclusion: We conclude that the strongly increased urinary excretion 8-oxo-7,8=dihydro-2′-deoxyguanisine indicates elevated lipid peroxidation induced DNA damage in internal organs such as the liver. These highly pro mutagenic lesions may contribute to the increased risk of thalassemia patients to develop hepatocellular carcinoma.